Asesmen Model dan Struktur Rumah Prafabrikasi Tahan Gempa Untuk Korban Bencana Indonesia - Mulyadi Mulyadi; Sheila Hani (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2026)
Indonesia is highly vulnerable to natural disasters, particularly earthquakes, tsunamis, and landslides, which frequently cause severe infrastructural damage and widespread displacement. The provision of post-disaster emergency housing is often constrained by time limitations, budget constraints, and construction standards. This study assesses whether earthquake-resistant prefabricated houses produced by Kinghouse Modular House Technology Co., Ltd., Guangzhou, China, are suitable for Indonesia’s geographical and social conditions and its building standards (SNI 1726:2019). The methodology encompasses coordination, literature reviews, direct observation of the production process, technical analysis of design and structure, and the formulation of adaptation recommendations. The assessment results indicate that the Kinghouse modular house—utilizing a galvanized C-channel steel frame, EPS sandwich panels, bolted connections, and anti-corrosive roofing—offers key advantages, including a lightweight structure and ease of assembly, making it highly feasible for implementation in disaster-prone areas. The primary recommendations include design modifications to align with national standards, material adjustments for tropical climates, and the development of multifunctional modular units. This study provides technical and strategic contributions for the government, industry, and the community in procuring rapid, safe, and sustainable post-disaster housing.